Beyond Traditional Testing: Exploring the Efficacy of Adaptive Assessments in Shaping Future Learners - Moses Adeleke Adeoye; Entika Fani Prastikawati; Rika Riwayatiningsih (Journal of Nonformal Education, 2025)
This study investigates the impact of adaptive assessment tools on student learning outcomes, engagement and knowledge retention compared to traditional assessment methods. The research employs a descriptive survey design, utilising a quantitative research approach to gather data from 200 students across various educational settings in Kwara State, Nigeria. The primary research questions explore how adaptive assessments influence knowledge retention, engagement levels and the identification of areas needing additional support. By focusing exclusively on students as respondents, the study reliable data that elucidates the effectiveness of adaptive assessments in enhancing knowledge retention and engagement within educational settings. The findings reveal that adaptive assessments significantly enhance knowledge retention, as indicated by mean scores above the established cut-off point of 3.0 across all survey items. Students reported high levels of engagement, motivation and clarity regarding their learning needs when using adaptive tools. In contrast, traditional assessments received notably lower scores, suggesting limited effectiveness in fostering positive learning experiences. The study concludes that adaptive assessment tools provide a more personalised and effective approach to student learning, leading to improved outcomes in both knowledge retention and engagement. It is recommended that educators integrate adaptive assessments into their curricula to maximise student learning potential. Policymakers should consider supporting the implementation of adaptive technologies in educational institutions to enhance the overall learning experience. The research contributes to the theoretical understanding of personalised learning approaches and offers empirical evidence supporting the effectiveness of adaptive assessments in contemporary education.